2010
DOI: 10.1016/j.jneumeth.2010.01.014
|View full text |Cite
|
Sign up to set email alerts
|

MR connectomics: Principles and challenges

Abstract: a b s t r a c t MR connectomics is an emerging framework in neuro-science that combines diffusion MRI and whole brain tractography methodologies with the analytical tools of network science. In the present work we review the current methods enabling structural connectivity mapping with MRI and show how such data can be used to infer new information of both brain structure and function. We also list the technical challenges that should be addressed in the future to achieve high-resolution maps of structural con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
209
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 256 publications
(213 citation statements)
references
References 106 publications
(126 reference statements)
3
209
0
1
Order By: Relevance
“…Over the last years it has become clear that MR based connectomic techniques are of the highest interest for the neuroscience community (Bassett et al, 2010;Bullmore and Sporns, 2009;Fornito et al, 2010;Gross, 2008;Hagmann et al, 2010;Zalesky et al, 2010), but methodological issues remains. The presented method is a contribution to tackle these issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last years it has become clear that MR based connectomic techniques are of the highest interest for the neuroscience community (Bassett et al, 2010;Bullmore and Sporns, 2009;Fornito et al, 2010;Gross, 2008;Hagmann et al, 2010;Zalesky et al, 2010), but methodological issues remains. The presented method is a contribution to tackle these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusionbased connectivity has also been used in some studies (Behrens and Johansen-Berg, 2005;Klein et al, 2007;Tomassini et al, 2007) to parcellate gray matter. In order to emphasize the importance of whole brain connectivity, the term connectome has been coined by our group as early as 2005 (Hagmann, 2005;Hagmann et al, 2010;Sporns, 2008;Sporns et al, 2005). It refers to the complete description of the structural connectivity of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…More generally, the current lack of empirical evidence for functional correlates of most network measures precludes neurobiologically grounded conclusions of functional network abnormalities and makes empirical validation of these interpretations a high priority. Such validation could, for instance, involve direct comparisons of structural and functional brain connectivity in the same individuals (Hagmann et al, 2010;Van Dijk et al, 2010) or the study of relationships between structural and functional connectivity in biologically realistic large-scale computational models of the brain (Deco et al, 2011).…”
Section: Review Of Van Den Heuvel Et Almentioning
confidence: 99%
“…Recently, the results reported in the literatures (Richiardi et al 2011;Shirer et al 2012) suggest us that functional connectivity is a new, alternative school of methodologies for quantitatively measuring functional brain response. Essentially, brain function is resulted from large-scale functional connectivities (Haynes and Rees 2006;Lynall et al 2010;Friston 2009;Hagmann et al 2010). The brain's comprehension of visual stimuli can be precisely represented by these functional connectivities and interactions among relevant brain networks (Friston 2009;Hagmann et al 2010;Lynall et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Essentially, brain function is resulted from large-scale functional connectivities (Haynes and Rees 2006;Lynall et al 2010;Friston 2009;Hagmann et al 2010). The brain's comprehension of visual stimuli can be precisely represented by these functional connectivities and interactions among relevant brain networks (Friston 2009;Hagmann et al 2010;Lynall et al 2010). Notably, a few recent studies (Hu et al 2012;Han et al 2013) have demonstrated that functional connectivity is an effective tool to model brain response to free viewing of videos.…”
Section: Introductionmentioning
confidence: 99%